The Relationship Between the Use of Ice-Breaking Activities in Learning and the Reduction of Academic Stress Among Elementary School Students - Ellya Rahma; Tri Shandra Abridinata Wibowo (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aimed to examine the relationship between the use of icebreakers in learning and the level of academic stress among elementary school students. Academic stress often arises due to monotonous learning methods and high academic demands, so a strategy that creates a pleasant learning atmosphere is needed. This research employed a quantitative, descriptive-correlational approach. The participants were 25 fifth-grade students from SD Negeri 01 Tugu Harum, comprising 12 boys and 13 girls. The instrument used was a 5-point Likert-scale questionnaire on the use of icebreakers and academic stress, which had undergone validity and reliability testing. Data were analyzed using Pearson's correlation, t-test, and the coefficient of determination. The results revealed a strong and significant relationship (r = 0.649; p < 0.05), with ice breaking contributing 42.1% to reducing academic stress. Although the sample size was limited, these findings emphasize that consistent application of icebreakers can be an effective strategy to support students' mental health and improve learning quality.